Ambiente virtual de aprendizagem em reumatologia pediátrica para residentes em pediatra: efetividade e índices de satisfação - Cunha, Ana Luiza Garcia [UNIFESP] (2017)
Introduction: Pediatric residents access to training in Pediatric Rheumatology is deficiente even in developed countries, where 40% of pediatric residency programs do not have this specialty in the curriculum. In Brazil, this problem is even greater, since reference centers are scarce. In addition, it is estimated that up to 190,000 children and adolescents have some rheumatic disease. Since Pediatricians are responsible for the first care and eventual referral, we must use all the resources for a more targeted education for the main rheumatic diseases of childhood and adolescence. Objectives: To elaborate, implement and evaluate a virtual learning environment (VLE) online in Pediatric Rheumatology, aimed at Pediatric residents, analyzing their effectiveness and satisfaction indexes. Methods: A total of 92 pediatric residents of the first and second year of Hospital Infantil João Paulo II (n = 44) and Universidade Federal de São Paulo (n = 48) were invited to participate in the study. Residents were randomized into a case group (who responded to the pre-course test, attended the six virtual pediatric rheumatology modules, with selected topics and content drawn from expert experience, and then responded to the post-course test and a satisfaction questionnaire) and control group (who did not had access to VLE and responded to the pre-course test and, after 4 weeks, responded to the post-course test). Results: Forty-seven residents (51% response rate) completed their articipation in the project. In the case group (n = 24), the mean percentage of correct answers was 14.05% [7.28%; 20.82%] higher in the post-course test when compared to the precourse test (p = 0.000). In the post-course test, there was a significant difference (p = 0.045) between the case and control groups (n = 23), and the mean percentage of correct answers was 8.41% [0.17%, 16.65%] higher in the case group. In the assessment of satisfaction with VLE use, residents considered the design of the site attractive (79%), with information distributed logically and clearly (83.3%) and easy navigation (91%). They reported poor prior knowledge in Pediatric Rheumatology (91%), and agreed that there was good learning in Pediatric Rheumatology through the methodology (75%), as well as the use of AVA as a learning tool (91%). Regarding the themes of the teaching modules, they were considered readable (> 90%), adequate (> 90%) and objective (> 90%). Conclusion: The virtual learning environment in Pediatric Rheumatology has proved to be an effective teaching tool with high levels of satisfaction in its use. This tool can be useful for spreading knowledge in Pediatric Rheumatology, providing the Pediatrician with an adequate knowledge for the initial assessment and conduct of patients with childhood rheumatic diseases.